A study of the application of performance management system in high-level weightlifting team - Fu, Y. -K.; Liu, M. -H. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume III: Statistics and Managment in Sports., 2008)
Based on the thorough analysis of the concept of performance management, this paper points out that, to high-level athletic teams, the sport performance can be enhanced by improving management approach and applying advanced management concept. Besides, in this paper, the corresponding performance management system has been designed for our national weightlifting team and the application of this system has proved very satisfactory.